Pangandaran Earthquake and b-value Analysis for Better Understanding of Seismic Vulnerability in Java using Statistical Earthquake Data of 2002-2010 - Wachidah, Siti Fauzatun; Wibawa, Agung; Ardhiansyah, Kurniawan; Syauqi, Muhammad (Diponegoro University Semarang Indonesia, 2025)
The application of statistical methods in seismicity analysis can provide a robust description of the relationship between earthquake magnitude and frequency in each region. This statistical relationship is formulated using the Gutenberg-Richter law, which continues to be developed through empirical and analytical studies of earthquakes in many regions. This study aims to analyze two significant earthquakes that affected the island of Java in 2006: the destructive Yogyakarta earthquake on 27 May 2006 and the Pangandaran earthquake on 17 July 2006. Both events were generated by active subduction mechanisms on the southern side of the island, where earthquakes of various magnitudes occur periodically. Through a temporal and spatial analysis of the b-value, this study compares different earthquake catalogs and analyzes the seismic vulnerability of Java by calculating the deformation caused by the 2006 earthquakes. The calculated b-values from the USGS and IRISDMC earthquake catalogs are 1.38 ± 0.04 and 0.92 ± 0.01, respectively. The magnitude of completeness (Mc) values are 4.9 for the USGS catalog and 4.3 for the IRISDMC catalog. The earthquake data span from 2002 to 2010. Deformation calculations using the IRISDMC data for 2006 show that the Pangandaran earthquake resulted in a surface rupture length of 140.60 km, a rupture area of 3,235.94 km², and a displacement of 7.96 m.